DNA-dependent protein kinase catalytic subunit: a target for an ICE-like protease in apoptosis. - Song, Q (1996)
Radiosensitive cell lines derived from X-ray cross complementing group 5 (XRCC5), SCID mice and a human glioma cell line lack components of the DNA-dependent protein kinase, DNA-PK, suggesting that DNA-PK plays an important role in DNA double-strand break repair. Another enzyme implicated in DNA repair, poly(ADP-ribose) polymerase, is cleaved and inactivated during apoptosis, suggesting that some DNA repair proteins may be selectively targeted for destruction during apoptosis. Here we demonstrate that DNA-PKcs, the catalytic subunit of DNA-PK, is preferentially degraded after the exposure of different cell types to a variety of agents known to cause apoptosis. However, Ku, the DNA-binding component of the enzyme, remains intact. Degradation of DNA-PKcs was accompanied by loss of DNA-PK activity. One cell line resistant to etoposide-induced apoptosis failed to show degradation of DNA-PKcs. Protease inhibitor data implicated an ICE-like protease in the cleavage of DNA-PKcs, and it was subsequently shown that the cysteine protease CPP32, but not Mch2alpha, ICE or TX, cleaved purified DNA-PKcs into three fragments of comparable size with those observed in cells undergoing apoptosis. Cleavage sites in DNA-PKcs, determined by antibody mapping and microsequencing, were shown to be the same for CPP32 cleavage and for cleavage catalyzed by extracts from cells undergoing apoptosis. These observations suggest that DNA-PKcs is a critical target for proteolysis by an ICE-like protease during apoptosis.